Birth distribution in cystic fibrosis in Saguenay-Lac-St-Jean, Quebec, Canada. Issue 9 (September 1991) - Daigneault, J; Aubin, G; Simard, F; De Braekeleer, M
Abstract : Although a seasonal trend in the birth distribution has been reported in cystic fibrosis (CF), this finding is still very controversial. The birth distribution of 113 patients with cystic fibrosis born in Saguenay-Lac-St-Jean (complete ascertainment) was analysed using two different statistical methods. Our results showed no monthly or seasonal birth variation. It is likely that a bias owing to incomplete ascertainment might explain why some previous studies found a seasonal trend in the birth distribution of cystic fibrosis.